PENGARUH PUPUK ORGANIK PADA TANAH LIAT TERHADAP PRODUKSI RUMPUT RAJA (Pennisetumpurpuroides) SEBAGAI PAKAN TERNAK RUMINANSIA - Sujarwo Sujarwo; Irine Ike Praptiwi; Dirwan Muchlis (Musamus Journal of Livestock Science, 2019)
This research aims to know the influence of the concentration of organic fertilizer of soil on the production of King grass (Pennisetumpurpuroides). This research using methods of randomized block design 3x2 treatment with 3 replicates. Treatment of I = K1L1 (clay fertilizer dose is 6 kg/plot), II treatment = K1L2 (clay fertilizer dose is 12 kg/plot), treatment of the III = K1L3 (clay fertilizer dose 18 kg/plot). The parameters observed were brangkas wet weight (height of plants, number of stem per block, number of leaves, stem diameter, heavy wet per block), heavy wet leaves and dry weight of leaves. The results of the study increased the wet weight and dry weight of K1L3 with an average weight of 3,200 grams and dry weight. 440.1 grams. Key Word : Organicfertilizer; soil type; production; king grass